Chromosomal localization of mutated genes in non-syndromic familial thyroid cancer - Yu-jia Jiang; Yun Xia; Yun Xia; Zhuo-jun Han; Yi-xuan Hu; Tao Huang (Frontiers in Oncology, 2024)
Familial non-medullary thyroid carcinoma (FNMTC) is a type of thyroid cancer characterized by genetic susceptibility, representing approximately 5% of all non-medullary thyroid carcinomas. While some cases of FNMTC are associated with familial multi-organ tumor predisposition syndromes, the majority occur independently. The genetic mechanisms underlying non-syndromic FNMTC remain unclear. Initial studies utilized SNP linkage analysis to identify susceptibility loci, including the 1q21 locus, 2q21 locus, and 4q32 locus, among others. Subsequent research employed more advanced techniques such as Genome-wide Association Study and Whole Exome Sequencing, leading to the discovery of genes such as IMMP2L, GALNTL4, WDR11-AS1, DUOX2, NOP53, MAP2K5, and others. But FNMTC exhibits strong genetic heterogeneity, with each family having its own pathogenic genes. This is the first article to provide a chromosomal landscape map of susceptibility genes associated with non-syndromic FNMTC and analyze their potential associations. It also presents a detailed summary of variant loci, characteristics, research methodologies, and validation results from different countries.